Association between the non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) and cognitive impairment in patients with acute mild ischemic stroke - Huiting Wang; Jingru Wang; Depeng Feng; Lin Wang; Jingjing Zhang (European Journal of Medical Research)
Abstract Background The non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a recently developed lipid parameter, but there are insufficient studies exploring its relationship with early cognitive impairment in patients with acute mild stroke. This study aims to determine the potential association between NHHR and early cognitive impairment in patients with acute mild stroke. By collecting data from patients with acute minor ischemic stroke in hospital, we will analyze the relationship between NHHR and cognitive function in these patients. Methods This study enrolled 817 acute ischemic stroke (AIS) patients (NIHSS ≤ 5), Cognitive function was assessed using Mini-Mental State Examination (MMSE) within 2 weeks, with cognitive impairment defined by education-stratified thresholds. Statistical analysis of the baseline was performed. Multivariate logistic regression was performed to analyze the association between NHHR and cognitive impairment, and Receiver Operating Characteristic Curve (ROC) analysis were performed to evaluate the predictive value. Results Patients were classified into cognitive impairment group (n = 473) and normal cognition group (n = 344). NHHR in the cognitive impairment group was significantly higher than that in the normal group (3.24 ± 1.63 vs. 3.02 ± 1.43, P = 0.046). There were significant differences in age and education level. There was a dose–response relationship between NHHR quartiles and the incidence of cognitive impairment (trend test P = 0.021). Multivariate regression analysis showed that for each unit increase in NHHR, the risk of cognitive impairment increases by 13.2% (OR = 1.13, 95% confidence interval 1.02–1.25, P = 0.018). The predictive model constructed by combining age and education level has an area under the ROC curve(AUC) of 0.71 (95% confidence interval 0.67–0.74). Conclusions NHHR is an independent risk factor for early cognitive impairment in mild AIS patients. The NHHR-based model demonstrates moderate predictive accuracy, supporting its potential clinical utility.